Liver stiffness and thrombin generation in compensated cirrhosis. Issue 2 (28th January 2019) - Dillon, Audrey; Egan, Karl; Kevane, Barry; Galvin, Zita; Maguire, Patricia; Ní Áinle, Fionnuala; Stewart, Stephen
Abstract: Background: Decompensated cirrhosis is associated with coagulation abnormalities that can increase the risk of thrombosis and bleeding. It is unclear precisely when these abnormalities arise and whether they are exacerbated as compensated cirrhosis progresses. Transient elastography using FibroScan generates liver stiffness measurements (LSM) that associate with portal hypertension, clinical outcomes and provides prognostic information at an earlier stage than traditional liver function scores eg, MELD score. Objective: To characterize thrombin generation in patients with compensated cirrhosis and to determine whether parameters of coagulation change throughout compensated cirrhosis, staged using LSM. Patients/Methods: Blood samples were collected from well‐compensated cirrhotic patients n = 61, All Child Pugh A stage) attending the Mater Misericordiae University Hospital, Ireland. Comprehensive clinical staging of liver disease, including LSM, was performed. Tissue Factor‐stimulated thrombin generation was measured by calibrated automated thrombography. Results: Using LSM to stage well‐compensated cirrhotic patients, we demonstrate a significant decrease in the rate of propagation, the rate of attenuation, and total thrombin generation as LSM increase. LSM correlated with endogenous thrombin potential, peak thrombin generation, the rate of propagation, and the rate of attenuation. This association between thrombin generation and LSM was still evident in sub‐analyses excluding patients with ongoing alcohol use, active HCV infection, or a history of decompensation. In contrast, there was no significant correlation between thrombin generation, prothrombin times, Child‐Pugh scores, or MELD scores. Conclusion: Liver stiffness measurements identify differences in parameters of thrombin generation within a cohort of compensated cirrhotic patients before changes in clotting times occur.